Patterns of care and outcomes of adjuvant therapy for high‐risk head and neck cancer after surgery. Issue 6 (16th February 2018) - Osborn, Virginia Wedell; Givi, Babak; Rineer, Justin; Roden, Dylan; Sheth, Niki; Lederman, Ariel; Katsoulakis, Evangelia; Hu, Kenneth; Schreiber, David
Abstract: Background: Postoperative chemoradiotherapy (CRT) is considered standard of care in patients with locally advanced head and neck cancer with positive margins and/or extracapsular extension (ECE). Methods: The National Cancer Data Base (NCDB) was queried to identify patients with squamous cell carcinoma of the head and neck with stages III to IVB disease or with positive margins and/or ECE diagnosed between 2004 and 2012 receiving postoperative radiotherapy (RT). Using univariable and multivariable logistic and Cox regression, we assessed for predictors of CRT use and covariables impacting overall survival (OS), including in a propensity‐matched subset. Results: Of 12 224 patients, 67.1% with positive margins and/or ECE received CRT as well as 54.0% without positive margins and/or ECE. The 5‐year OS was 61.6% for RT alone versus 67.4% for CRT. In the propensity‐matched cohort, OS benefit persisted with CRT, including in a subset with positive margins and/or ECE but not without. Conclusion: Postoperative CRT seems underutilized with positive margins and/or ECE and overutilized without positive margins and/or ECE. The CRT was associated with improved OS but the benefit persisted only in the subset with positive margins and/or ECE.